ANALISIS KONJOIN FULL PROFILE DALAM PEMILIHAN BEDAK UNTUK MAHASISWI DEPARTEMEN STATISTIKA UNIVERSITAS DIPONEGORO - Julianisa, Rose Debora; Safitri, Diah; Yasin, Hasbi (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Powder is the one of cosmetic product that serves to cover the shortfall on the face. Powder consumption continues to increase from year to year to follow trend of cosmetic and lifestyle that happened to people. It makes producer to be more creative and innovative to produce or developing their product to keep consumers interested. To help producer to know and understand the consumer preference on combinations of attributes in the powder, it can be used conjoint analysis. Beside that, conjoint analysis is used to get the concept of products that comply with the consumers want and can be developed as a combination of new products. In this thesis conjoint analysis is used by using presentation method of full-profile. There are four attributes used in this analysis, they are powder types, form of packaging, aroma, and glass facility. From the results of the analysis that obtained by the respondents, the most importance attribute in selecting a face powder is the package attribute (34,338 %), the second is a kind of powder (33,667 %), the third is glass facility in the powder (16,397 %), and the last is the scent of powder (15,598 %). The combination of desired respondents in choosing or use a powder is a powder that have the type of compact powder, circular packaging forms, has no aroma, and there is no glass. Keywords : powder, consumer’s preference, conjoint analysis, full-profile